Balaghah Rhetoric in the Sermon of Hani’ bin al-Qabishah: A Study of Arabic Stylistics - Abrory, Mochamad Iqbal Aqil; Birrohman, Teguh Iman; Pujonugroho, Hananda Satrio (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Khutbah is a form of literary work that has existed since the Jahiliyyah (pre-Islamic) era. Its presence is the result of the orator’s creative process in selecting words, formulating ideas, and delivering language both explicitly and implicitly. During the Jahiliyyah period, khutbahs often reflected the circumstances and conditions of ancient Arab society, specifically the pre-Islamic Arab community. At that time, the khutbahs delivered conveyed ideologies, hopes, and advice intended to influence and express the orator’s intentions. One such khutbah was delivered by Hani’ bin Al-Qabishah to his tribe, the Banu Bakr. The khutbah contains deeply meaningful words calling for the tribe to rise up and fight against the Persian army. This study uses a descriptive qualitative method with an Arabic stylistic approach that focuses on linguistic aspects, including rhetorical appropriateness and the beauty of meaning. The researcher aims to uncover the aesthetic value of the meanings and words systematically arranged in accordance with linguistic principles. A deep understanding of literary works cannot be separated from the context in which the events occurred, including historical, sociocultural, and biographical aspects of the orator. This beauty is further emphasized by the fact that it would be nearly impossible for people today to compose literary works with such profound and admirable meaning as in the Jahiliyyah era, a time before the emergence of linguistic sciences.